(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: patients with Ankylosing Spondylitis (AS) usually suffer from diagnostic delay. having symptoms up to several years before correct diagnosis, leading to psychological distress , physical and healthcare burden.Objective: To measure the period of diagnostic delay of AS and explore the main causes of diagnostic delay.Patients and Methods: A forty –eight consecutive patients (41 males , 7 females),the mean age 34.4 ±8.54 years (ranging from 18 to 58 years) with AS who met the modified New York 1984 criteria were enrolled in this cross sectional study, which have been conducted at Merjan teaching hospital, Rheumatologic and rehabilitation out-patient department in Babylon from period January 2018 to July 2019. The diagnostic delay was defined as the interval between appearance of first symptoms and correct diagnosis of AS was measured (in years) for each patient. Full detailed history of each patient about her/his journey of previous diagnosis and treatment measures were recorded.Results: The mean of diagnostic delay was 8.47±6.15 years in males, and 10.1± 8.62 years in females. The most common missed diagnoses contributing to delay diagnosis of AS were : non-specific back pain (22 patients, 45.8%), degenerative disease ( lumbar spondylosis) ( 10 patients, 20.8 %) disc prolapse (12 patients, 25%), sacroiliac sprain (2 patients 4.16%), rheumatoid arthritis (1 patient, 2.17%), and chronic brucellosis ( 1 patient 2.17%) .Conclusion: Most patients had obvious diagnostic delay prior to definite AS diagnosis which could have been avoided with earlier intervention.